2011
DOI: 10.1557/jmr.2011.208
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between yield point phenomena and the nanoindentation pop-in behavior of steel

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 42 publications
5
14
0
Order By: Relevance
“…In those studies, pop-ins disappeared after the introduction of small amounts of plastic deformation [136]. Therefore, in the prior studies, it was concluded that the pop-ins were a consequence of the difficulty of activating dislocation sources within the primary indentation deformation zone [54,[120][121][122]124,125]. In the present work, the lack of pop-ins in the 810-10-000 sample is consistent with the previous observations described above.…”
Section: Nanoindentation and Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In those studies, pop-ins disappeared after the introduction of small amounts of plastic deformation [136]. Therefore, in the prior studies, it was concluded that the pop-ins were a consequence of the difficulty of activating dislocation sources within the primary indentation deformation zone [54,[120][121][122]124,125]. In the present work, the lack of pop-ins in the 810-10-000 sample is consistent with the previous observations described above.…”
Section: Nanoindentation and Resultssupporting
confidence: 90%
“…A pop-in is identified as a sudden jump in the indentation displacement at a roughly constant load (the tests are performed in load control) and appears as a strain burst in the indentation stress-strain curves (see the measurement for the ferrite region in Figure 7). Pop-in events have been observed extensively in previous work [54,[120][121][122][123][124][125] and were attributed to the difficulty of activating dislocation sources in the very small primary indentation zone. These pop-ins make it difficult to accurately estimate the indentation yield strength.…”
Section: Nanoindentation and Resultsmentioning
confidence: 80%
“…Apart from transmission electron microscopy, one of the most successful recent methods delivering direct evidence for dislocation activity in the metals is nanoindentation [18][19][20][21][22][23][24][25][26][27]. During the nanoindentation of perfectly prepared samples with a very low dislocation density, it is possible to observe a homogeneous dislocation nucleation (HDN) below the surface in the volume.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon could be related to high mobile dislocation density without pinning effect of carbons or precipitates [ 50 , 51 , 52 , 53 ]. On the contrary, some previous studies have shown discontinuous yielding after tempering or ageing [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. It is well accepted that discontinuous yielding is caused by unpinning of dislocation from the Cottrell atmosphere, which formed by the interaction between dislocation and interstitial atoms such as carbon and nitrogen [ 52 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 84%
“…On the contrary, some previous studies have shown discontinuous yielding after tempering or ageing [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. It is well accepted that discontinuous yielding is caused by unpinning of dislocation from the Cottrell atmosphere, which formed by the interaction between dislocation and interstitial atoms such as carbon and nitrogen [ 52 , 54 , 55 ]. Heat treatment could induce diffusion of interstitial atoms into the dislocation core so dislocation is pinned during deformation and able to escape from the atmosphere by reaching the upper yield point.…”
Section: Resultsmentioning
confidence: 84%